Excavatolide E triggers oxidative stress-associated apoptosis and DNA damage to inhibit bladder cancer cell proliferation - Che-Wei Yang; Chia-Hung Yen; Tsu-Ming Chien; Szu-Yin Yu; Fang-Rong Chang; Jyh-Horng Sheu; Hsueh-Wei Chang (Molecular Biology Reports, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

Temperature-influenced deformation analysis of a full-scale steel-concrete-steel cable support tower model during construction - Zhi-Li Qi; Wei-Le Chen; Jian Li; Jian-Sheng Fan; Rong Xian; Fei Tian; Yu-Fei Liu (Engineering Structures, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Spatiotemporal dynamics of PFAS ecological risk in major Chinese river networks: a data-driven assessment (2011–2024) - Letian Zhang; Wei Lin; Zhouyun Xie; Yewei Wang; Rong Wu; Jiaqi Yang; Nanyang Yu; Xiaodong Li; Jie Liang (Water Research, 2026)

Typhoon-induced ocean wave noise as a natural source for passive MASW: Insights from DAS observations - Jia-Wei Liu; Rong-Huei Chen; Ya-Mei Yang; Chung Haung; Ting-Yu Bai (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

Epinephelus coioides lnc32039 promotes the infection of iridovirus SGIV via inhibiting immune response and apoptosis - Yin-Mei Lan; Wen-Feng Yang; Yu-Qin Ma; Yu-Rong Lei; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2026)

Integrated network toxicology, transcriptomics, and metabolomics revealed the potential mechanisms of aluminum-induced testicular injury - Siyu Liao; Liqing Huang; Yusi Zhou; Xin Zhang; Shaofeng Huang; Linjun Yu; Shiman Zhu; Wei Chen; Rong Wang; Haimei Qin (Food and Chemical Toxicology, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Temporal changes of soil erodibility and its driving factors in long-term sugarcane continuous cropping systems - Juan Wei; Tieguang He; Yu Zhu; Lirong Su; Huiping Ou; Yingying Deng; Mengge Yang; Jinlong Chang; Yuliang Liao; Qingbiao Rong; Yuhan Huang (CATENA, 2026)

Decadal Resampling Reveals Widespread Increases in Soil Microbial Diversity Associated With Nitrogen Deposition - Yi Fan; Yiheng Tao; Bin Hua; Paul Kardol; Yakov Kuzyakov; Shuang Pang; Yi Wu; Tingling Li; Wei Yang; Honghui Wu; Anton A. Goncharov; Anastasia Yu. Korotkevich; et al. (Global Change Biology, 2026)
Simulated manipulation experiments, such as nitrogen addition to mimic atmospheric nitrogen deposition, are widely used in global change research. However, experimental manipulations may differ from real‐world environmental change in their intensity, duration, and co‐occurrence, leaving long‐term changes in soil microbial communities and soil health insufficiently understood. To address this gap, we resampled soils from 38 forest and grassland ecosystems across eastern China in 2009 and 2019 and assessed microbial taxonomic and functional diversity using shotgun metagenomics. Microbial diversity increased by 17% over the decade, accompanied by clear shifts in community composition. Among the environmental variables considered, nitrogen deposition (~19 kg nitrogen ha −1 year −1 across ecosystems) was the strongest predictor of changes in seven of 12 microbial community metrics. Larger nitrogen deposition was also associated with increased relative abundances of nitrogen‐cycling genes and reduced spatial turnover in microbial community composition. These effects were consistent with a potential alleviation of nitrogen limitation and weakening of deterministic community assembly, although these mechanisms could not be directly established. In addition, increases in genes associated with carbon degradation and phosphorus cycling, together with declines in the relative abundances of pathogens, antibiotic resistance genes, and DNA viruses, coincided with the raise of the composite soil health index. Our findings demonstrate widespread decadal increases in soil microbial diversity and soil health across eastern China, with nitrogen deposition emerging as their strongest environmental factor. These results highlight that microbial responses to long‐term ambient environmental change can differ markedly from responses inferred from short‐term or high‐intensity manipulation experiments.

Dysregulation of xenobiotic metabolism and mitochondrial dysfunction exacerbate acetaminophen-induced hepatotoxicity in human antigen R-deficient male mice - Natalie Eppler; Elizabeth Jones; Forkan Ahamed; Naren Raja; Jephte Y. Akakpo; Margitta Lebofsky; Lily He; Ira Vats; Priyanka Ghosh; Yifan Yu; Kaitlyn Thomas; Colin McCoin; et al. (Toxicology, 2026)

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

Perfluorohexane sulfonate (PFHxS)-induced energy metabolism disruption in Chlorella pyrenoidosa: Integrating physiological and transcriptomic insights - Biao Liao; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Shan Liu; Ji-Xun Chen; Liu-Yi Wei; Xiang-Rong Xu; Kefu Yu (Environmental Pollution, 2026)

An AI-informed framework for flavor design: How κ-carrageenan sculpts low-sodium myofibrillar protein architecture for aldehyde capture and bitterness masking - Rong Huang; Yapeng Fang; Hao Yin; Yu Zhong; Wei Lu; Linnan Yang; Yun Deng (Carbohydrate Polymers, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Partitioned identification of vegetation drivers and their interactions in the Loess Plateau via interpretable XGBoost-SHAP - Yi Ren; Jia Tian; Xuejuan Feng; Guowei Wu; Caifeng He; Wei Bao; Tao Yu; Jiahui Gao; Tao Wang; Jian Wen; Rong Tao (Environment, Development and Sustainability, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Effects of hypoxia-inducible factor prolyl hydroxylase inhibitors on lipid profiles in patients with chronic kidney disease: a systematic review and meta-analysis - Yun-Hui Huang; Yu-Han Huang; Tzu-Rong Peng; Ta-Wei Wu (European Journal of Clinical Pharmacology, 2026)

Non-contact effects of the parasitoid Sclerodermus guani on its two cerambycid host species - Yu-jun Kong; Yong-hao Nan; Hui-quan Sun; Ke Wei; Jian-rong Wei (BioControl, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Evaluation of protein and metabolic engineering strategies on (−)-α-bisabolol production by Escherichia coli - Jiayi Ma; Rong Fang; Xiaoyuan Yue; Hui Jiang; Qixuan Kong; Tiankuo Jiang; Jiale Yu; Chang Zhou; Yuanyuan Xia; Wei Shen; Haili Liu; Yaqin Shen; et al. (Systems Microbiology and Biomanufacturing, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

Climate resilience of grain production in China: measurement, dynamic evolution, and spatial spillover effects - Mingliang Li; Rong Kong; Jiyu Wei; Yuanyuan Xiong; Guoxin Yu (Environment, Development and Sustainability, 2026)

Is ecological quality of river-connected lake basin higher than disconnected lake basins in the lower reaches of the Yangtze River, China? - Dong-zheng Yu; Ying Huang; Jing-wei Yang; Xiang-rong Song; Xin-sheng Chen (Environmental Monitoring and Assessment, 2026)

Influence of Trailing Suction Hopper Dredger Side-Casting Backfilling Parameters on Far-Field Plume Dispersion and Deposition of Sediments - Hongwen Zheng; Diqing Rong; Mingjie Yu; Dongliang Meng; Tao Sun; Wei Wei (Journal of Marine Science and Engineering, 2026)
Layered side-casting backfilling performed with a trailing suction hopper dredger (TSHD) is widely used in tidal waters, but its continuous moving release can generate a time-varying far-field sediment plume that complicates both backfilling control and environmental impact assessment. To investigate how construction parameters affect far-field sediment dispersion and deposition under side-casting conditions, this study develops a two-dimensional hydrodynamic–sediment coupled numerical model with a mass-conserving moving-source term for a tidally dominated coastal area. Model performance was evaluated against field observations, yielding NRMSE/MRAE values of 0.0787/6.03% for water level, 0.2249/18.30% for current speed, 0.2344/27.10% for suspended-sediment concentration (SSC), and 0.1230/11.10% for deposition thickness; the correlation coefficient for current speed was 0.904. Based on the validated model, scenario analyses were conducted for different combinations of sailing speed and sediment concentration. The results show that far-field plume evolution exhibits pronounced stage-dependent behavior, with the largest affected footprint generally occurring during the late operational period or shortly after source termination. Within the tested parameter space, sailing speed has a stronger influence on the dispersion scale and SSC recovery duration because it controls both the release duration and source sweeping rate. Sediment concentration more directly affects deposition-related responses, including deposited thickness, lateral coverage, and along-track continuity, although its incremental effects weaken in the high-concentration range and remain coupled with sailing speed. Dimensional analysis further suggests that the relative magnitudes of source duration, advection, and settling timescales help explain the differences among scenarios. These results provide a physically based reference for parameter selection and construction planning in layered side-casting backfilling under tidal forcing.

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Synergistic κ-Carrageenan/KCl modulation of myofibrillar protein gelation: decoding gel structure-bitterness masking intrinsic correlation via multimodal neural network - Rong Huang; Yapeng Fang; Hao Yin; Yu Zhong; Wei Lu; Yun Deng (Food Hydrocolloids, 2026)

Nitrogen doped graphene quantum dots modified a crystalline zinc phosphite based non-enzymatic electrochemical sensor for the ultra-low detection of tyramine - Pi-Chen Wei; Asit Kumar Panda; Yu-Chung Chang; Yi-Rong Li; Todd Hsu; Chih-Min Wang (Food Control, 2026)

Genome-wide CRISPR/Cas9 knockout screen identifies host factors essential for bovine parainfluenza virus type 3 replication - Jinyang Hao; Xiaoran Gao; Christine Light; Yuze Sun; Sha Lu; Yu Tian; Xia Gao; Yuan Su; Jie Gao; Xin Huang; Qianyi Zhang; Jinliang Wang; et al. (Science China Life Sciences, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Pharmaceutical-dominated organic contaminants in plateau lakes: Suspect and non-target screening, PBT risk, and structure-based risk markers - Liben Chou; Wanshu Zhu; Rong Zhang; Jinsha Jin; Kai Huang; Lu Dong; Mengke Jin; Wenrui Luo; Yan Mao; Xiangyi Yu; Haoyue Tan; Jing Guo; et al. (Water Research, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

PM2.5-modulated targets and miRNAs associated with lung cancer and injury are protected by natural products - Ya-Ting Chuang; Ching-Yu Yen; Wangta Liu; Fang-Rong Chang; Yi-Hong Tsai; Wen-Hsiung Chan; Tsu-Ming Chien; Hsueh-Wei Chang (Environmental Pollution, 2026)

Cold adaptation strategies of anammox bacteria and the bottleneck of nitrogen removal performance in autotrophic nitrogen removal process treating digested swine wastewater - Ya-hui Wang; Fang-yu Huang; Long-xing Jiang; Rong You; Yun-hong Zhang; Liang-wei Deng; Wen-guo Wang; Lan Wang (Chemical Engineering Journal, 2026)

Automatic Detection of Disaster-Causing Organisms near the Waters of Nuclear Power Plant Based on LiveScope Scanning Sonar Images - Gangyi Yu; Shuo Wang; Wei Liu; Yongjian Xia; Yuchen Guo; Xiaolu Chen; Xueping Wei; Ao Chen; Zehua Lv; Chao Lu; Junbo Zhang; Rong Wan (Journal of Marine Science and Engineering, 2026)
Nuclear power serves as an efficient, clean, and low-carbon energy source that constitutes a significant component of the energy portfolio in numerous countries. Most nuclear power plants are predominantly situated in coastal regions, utilizing seawater as the ultimate heat sink for their cooling systems. Real-time monitoring of marine organism dynamics near water intakes is essential to mitigate the risk of unit shutdowns triggered by outbreaks of disaster-causing organisms (DCOs). This study employed LiveScope scanning sonar videos captured near the Ningde Nuclear Power Plant to develop a dataset for detecting the light spot area of the DCOs. We proposed a directionally optimized model, Bio-YOLO v7, which significantly enhances the detection of small targets in sonar images. The Bio-YOLO v7 model achieved precision, recall, and average precision rates of 85.29%, 83.28%, and 81.49%, respectively, demonstrating superior performance in identifying DCOs near the intakes of nuclear power plant. The light spot size of the DCOs exhibited significant periodic variations, serving as a crucial indicator for forecasting outbreak events.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

New C22-related terpenoid from Formosan marine sponge Lendenfeldia sp. - Quoc-Vu Pham; Hsin-Wei Wang; Yu-Cheng Chen; Yu-Chia Chang; You-Song Cheng; Yun-Shiuan Chen; Mei-Hsien Lee; Jui-Hsin Su; Bo-Rong Peng; Kuei-Hung Lai (Phytochemistry Letters, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

How human-perceived urban green spaces contribute to mental well-being: a machine learning approach - Enqi Cheng; Yuejing Rong; Yan Yan; Chenxing Wang; Lijie Wang; Yu Zhao; Zetong Wang; Wei Li (Journal of Environmental Management, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Efficient low-temperature NO reduction via constructing Cu+ −O−Co3+ sites to enhance lattice oxygen release and CO adsorption - He Wang; Ye Zhu; Wei Wang; Xiaoqing Dang; Yufei Zhang; Dandan Zhu; Rong Li; Dongjie Yan; Qian Ma; Jiaxin Qu; Jiaquan Zhang; Yu Huang (Journal of Hazardous Materials, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

One new rearranged pyranone derivative with antibacterial activity from Xylaria curta YSJ-5 - Shan-Shan Wei; Dao-Jun Rong; Jia-Ying Lai; Chen Chen; Si-Ran Li; Zhong-Hua Yu; Hai-Bo Tan (Phytochemistry Letters, 2025)

Advances in acetylcholinesterase-based biosensing technologies for organophosphorus pesticide detection: A comprehensive review (2020–2024) - Qian Zhang; Jing Yu; Yanping Wei; Rong Yang; Jin Liu; Yangyang Su; Die Gao; Jing Zeng (Food Chemistry, 2025)

Al-optimized synergy of KCl and κ-carrageenan in low-sodium sausages: Integrated enhancement of saltiness perception, gel stability, and protein digestibility - Rong Huang; Yapeng Fang; Hao Yin; Yu Zhong; Wei Lu; Yun Deng (Food Hydrocolloids, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Adaptive responses of soil phosphorus availability and plant phosphorus resorption to nitrogen enrichment-induced phosphorus limitation in a boreal peatland - Yu-Xin Ji; Le-Lin Yu; Zhen Zeng; Xian-Wei Wang; Rong Mao (Plant and Soil, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Anti-acrolein from natural products by regulating miRNAs and targets - Ya-Ting Chuang; Ching-Yu Yen; Jen-Yang Tang; Yi-Hong Tsai; Fang-Rong Chang; Tsu-Ming Chien; Hsueh-Wei Chang (Journal of Hazardous Materials, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Decoupled motion planning method for 7-DOF manipulator and lifting joint in automated tomato harvesting - Jiacheng Rong; Yu Liu; Xianjun Li; Chao Gao; Pengbo Wang; Ting Yuan; Wei Li (Computers and Electronics in Agriculture, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Assessing 3-D variability of ultrafine particle using a Geo-AI modelling approach: A case study in Zhunan-Miaoli, Taiwan - Chia-Wei Hsu; Yinq-Rong Chern; Jun-Jun Su; Pei-Yi Wong; Aji Kusumaning Asri; Candera Wijaya; Yu-Cheng Chen; Shih-Chun Candice Lung; Ta-Chih Hsiao; Tee-Ann Teo; Yi-Liang Shih; Chih-Da Wu (Environmental Pollution, 2025)

A hydraulic conductivity model for unsaturated bentonite-based materials incorporating surface enhanced vapour diffusion - Zhang Rong LIU; Yu Jun CUI; Wei Min YE; Yong Gui CHEN; Qiong WANG (Computers and Geotechnics, 2025)

Integrated Biofilm Modification and Transcriptional Analysis for Improving Fengycin Production in Bacillus amyloliquefaciens - Chun-Yang Cao; Zheng-Jie Hou; Ming-Zhu Ding; Geng-Rong Gao; Bin Qiao; Si-Yu Wei; Jing-Sheng Cheng (Probiotics and Antimicrobial Proteins, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Biogenic Cu2-xSe nanoparticles with vacancy engineering quickly upcycle cobalt from wastewater for photothermal antibacterial and desalination - Xue-Meng Wang; Zhi-Xuan Zhang; Yun-Jie Wang; Hao-Yu Li; Wen-Wei Li; Rong Chen (Water Research, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Limited leaf thermal acclimation but higher tolerance in subtropical trees after 10-year translocation in Dinghushan biosphere reserve - Ting Wu; David T Tissue; Wei Su; Honglang Duan; Mark G. Tjoelker; Sachin G. Chavan; Shuyidan Zhou; Junfeng Yuan; Liang Fang; Mengxiao Yu; Shizhong Liu; Guowei Chu; et al. (Agricultural and Forest Meteorology, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Novel galactose-rich polysaccharide from Ganoderma lucidum: structural characterization and immunomodulatory activities - Zhou-Wei Wu; Xiao-Cui Liu; Chen-Xi Quan; Xin-Yu Tao; Yi-Luo; Xue-Fang Zhao; Xing-Rong Peng; Ming-Hua Qiu (Carbohydrate Polymers, 2025)

Spatiotemporal distribution and priority assessment of steroids in the estuarine environment: Implications for environmental risk management - Ru Xu; Nian-Nian Wu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Bing Hong; Shen Yu; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Antibiotics shape the core microbial community distribution between floc and biofilm in an endogenous partial denitrification system: Insight from metabolic pathway - Kai-Yue Dong; Chao-Xi Yang; Jin-Luo Pang; Rong-Rong Chang; Ke-Yu Chen; Wei Yao; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Technological advances and sustainable strategies for electrolytic manganese wastewater treatment: A critical review - Chenyang Zhang; Ronghao Du; Rong Wang; Wei Sun; Yueping Luo; Zhiyuan Yu (Process Safety and Environmental Protection, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A soil–water retention model with differentiated adsorptive and capillary regimes - Zhang-Rong Liu; Wei-Min Ye; Yu-Jun Cui; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Anthropogenic Influence on the Compound Hot and Dry Event in Summer 2022 in the Tibetan Plateau Based on Statistical Downscaling CMIP6 Models - Kening Xue; Wei Li; Siyan Dong; Rong Yu; Leibin Wang (International Journal of Climatology, 2025)
In the summer of 2022, the Tibetan Plateau experienced a record‐breaking compound hot and dry event (CHDE). This study quantifies the contribution of anthropogenic influence to this compound event using a set of high‐resolution statistical downscaling results from six CMIP6 models. The Copula function was used to calculate the joint probability of the compound event. The results show that in the summer of 2022, hot conditions in the Tibetan Plateau broke records since 1961, with a return period of 408 years. The dry conditions were also uncommon, with a return period of 47 years. The hot and dry compound event is particularly rare, with a return period of more than 20,000 years. Based on the results from statistical downscaling models, it was found that anthropogenic influence has increased the risks of dry and hot conditions similar to those in the Tibetan Plateau in 2022 by factors of 3.3 [1.5, 5.2] and 14 [8.6, 21.2], respectively. Additionally, the risk of compound events has been increased by a factor of 46.7 [26.7, 77.6]. In the future, with the intensification of warm‐wet situations on the Tibetan Plateau, the hot conditions similar to 2022 are expected to increase remarkably, with the risk of occurrence rising by factors of 56 [34, 108] and 75 [44, 162] during the periods 2021–2040 and 2051–2070, respectively. Conversely, dry conditions are projected to decrease, with reductions of 0.21 [0.075, 0.46] and 0.51 [0.3, 1.2] times in the two future periods. However, the risk of compound events is expected to increase, with increases of 3.3 [1.5, 5.2] times and 11 [6, 25] times during the two periods. This study is the first to use downscaled simulation to conduct event attribution analysis for the Tibetan Plateau, which can deepen the understanding of the influence of human activities on compound events.

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Climate warming will alter the impact of microplastics on the bioavailability of arsenic in a subtropical estuary - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Wei Yu; Rong Yu (Journal of Hazardous Materials, 2025)

Enhanced phosphate removal by lanthanum functionalization using zirconium-based metal organic frameworks: Role of in situ formed La(OH)3 - Suyu Kong; Meili Ding; Mengjiao Yu; Wei Rong; Yang Wang; Jianfeng Yao (Journal of Environmental Chemical Engineering, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

Marking and Deterring Oviposition on Parasitized Hosts by a Host-Marking Pheromone in an Egg Parasitoid - Zi-Yin Wang; Si-Yu Yin; Jian-Rong Wei; Lan-Fen Qiu; Hao-Yuan Hu; Peng-Cheng Liu (Journal of Chemical Ecology, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Interfacial clustering-derived fluorescent, mechanically strong and fire-safe epoxy composites - Dong-Qing Zeng; Xin-Miao Li; Feng Chen; Wei-Bin Bai; Yu-Cai Lin; Rong-Kun Jian (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Observed seasonal evolution and origins of the western Yellow Sea Cold Water Mass - Chuanjie Wei; Xiaohui Tang; Kai Ge; Anqi Xu; Yuanlong Li; Yong Jiang; Zengrui Rong; Fei Yu (Frontiers in Marine Science, 2025)
The Yellow Sea Cold Water Mass (YSCWM) is one of the most prominent hydrological features of the Yellow Sea. As a low-temperature, nutrient-rich subsurface water mass, the YSCWM fundamentally regulates biogeochemical cycles, functions of marine ecosystems, and fishery resources of the YS. In boreal summer, the YSCWM shows a robust triple-core structure, in which the western component, dubbed the “western YSCWM”, is revisited in this study. Through analyzing in-situ observational data collected by research cruises of the Institute of Oceanology, Chinese Academy of Sciences (IOCAS) and Lagrangian tracing experiments based on a high-resolution ocean model, we provide a thorough investigation for seasonal evolution and origins of the western YSCWM. In-situ observations during 2006-2007 and 2014-2015 suggest that the western YSCWM bears a tight connection to the colder coastal waters near the Shandong Peninsula and achieves the coldest temperature in summer. Analysis of model simulations confirms that the cooling of the western YSCWM in spring and summer is caused mainly by southward cold-water transport of the Shandong Coastal Current (SDCC) from the Shandong coasts and the northern Yellow Sea. We also reveal a contribution of the Subei Shoal water via the Subei Coastal Current (SCC) in summer, which plays a critical role in the quick vanishing of the western YSCMW in early autumn. These findings contribute to our understanding of the formation, seasonal evolution, and heat budgets of the YSCWM.

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Research on Optimization Method for Irregular Seismic Acquisition in Curved Wave Domain Based on Simulated Annealing - Hu Zhao; Meng-yang Chen; Yu-dong Ni; Rong-rong Zhao; Fu-hao Jiang; Wei Chen; Jing-yun Dai (Applied Geophysics, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

Abundance Variability of Predators: Asynchronous Fluctuation of Tuna Species in the Atlantic Ocean due to Predation Strategies and Climatic Effects - Ting‐Yu Liang; Kuo‐Wei Lan; Muhamad Naimullah; Yen‐Rong Liang; Yan‐Lun Wu (Fisheries Oceanography, 2025)
Bigeye tuna ( Thunnus obesus ; BET) and yellowfin tuna ( Thunnus albacares ; YFT) are commercially and ecologically important Atlantic Ocean species. Numerous studies have examined interacting species with clearly synchronous or asynchronous dynamics, but few have investigated interactions among tuna species. This study investigated the effects of climate indices on the standardized catch per unit effort (CPUE) and habitat preferences of BET and YFT in the Atlantic Ocean. The indicators for both tuna species were found to be influenced by the Atlantic Multidecadal Oscillation (AMO) and Tropical North Atlantic index. The AMO had the strongest effect on standardized CPUE for the two species, and habitat suitability also reflected AMO trends. We compared CPUE trends in overlapping suitable habitat areas and estimated variations in primary prey abundance for between BET and YFT to evaluate their species' competition for limited prey and habitat area resources. The standardized CPUE, habitat suitability index (HSI), and primary prey levels (squid and crustaceans) of BET all increased following the change to the positive AMO phase after the 1990s. Although the HSI value for YFT also increased in an area of habitat overlap, the corresponding standardized CPUE decreased. We suggest that this pattern of a decreasing‐standardized CPUE for YFT may have been caused by competition for limited prey and habitat area resources in the overlap area.

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Enhanced carrier separation and photocatalytic degradation of oxytetracycline via S-scheme MIL-53(Fe)/FeOCl heterojunction composites with peroxydisulfate activation - Wei Dong; Chunyan Du; Yin Zhang; Jiao Cao; Jingyi Jiang; Lu Zhou; Guanlong Yu; Yulv Zou; Huaiyuan Peng; Rong Yan; Yu Yang (Journal of Environmental Chemical Engineering, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Effect of magnetic field-assisted thawing on the quality and microstructure of Portunus trituberculatus meat - Rong Shi; Zhongqi Sun; Xuemei Yu; Huamao Wei; Gaoshang Li; Wenge Yang (Food Research International, 2025)

Nonconventional phosphorus-based tertiary amine curing agent enabling the high fire safety, outstanding tensile strength and high glass transition temperature of epoxy resin - Xue-Qi Chen; Yu-Cai Lin; Wei-Bin Bai; Yuan-Wei Yan; Rong-Kun Jian (Chemical Engineering Journal, 2025)

Revealing microbial compatibility of partial nitritation/Anammox biofilm from sidestream to mainstream applications: Origins, dynamics, and interrelationships - Yanxiao Wei; Weizhe Xia; Yunzhi Qian; Chao Rong; Min Ye; Yujie Chen; Jun Kikuchi; Yu-You Li (Bioresource Technology, 2025)

Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hongjian Hao; Rong Wang; Shicai Li; Duo Pian; Ning Peng; Ahejiang Sailike; Zhouchang Yu; Jiayi Shi; Xingbo Wang; Zihan Wang; Wei Zhang (Plant and Soil, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

Analysis of extreme water levels on Feiyun River (Rui’an section) based on peaks-over-threshold (POT) model - Zipeng Qin; Yan Tian; Yanji Wei; Zhenglin Chen; Xiaoying Zhu; Qianfu Chen; Weixing Huang; Rong Yu; Xiang Cheng (Hydrological Sciences Journal, 2025)

Model-based analysis for investigating the impact of tumor size, lymphocyte and neutrophil on the survival of breast cancer 4T1 tumor-bearing mice - Qing-yu Yao; Xin-yu Hou; Wei-zhe Jian; Tian-yu Wang; Ping-yao Luo; Jun-sheng Xue; Rong Chen; Tian-yan Zhou (Toxicology and Applied Pharmacology, 2025)

Unveiling the molecular symphony: MicroRNA160a-Auxin Response Factor 18 module orchestrates low potassium tolerance in banana (Musa acuminata L.) - Yi Tang; Hang Rong; Xingchen Jia; Yinglong Chen; Zishu Wang; Jinyi Wei; Chenyi Yang; Jianfu Liu; Mingyuan Wang; Hailing Yu; Qizhi Wang (Plant Science, 2025)

Inhibition of fungal mycelial growth and mycotoxin production using ZnO@mSiO2 nanocomposite during maize storage - Song-Yue Xu; Zi-Yi Wang; Qiong Wu; Feng-Wei Hu; Jin-Feng Zhao; Yu-Rong Zhang; Dong-Dong Zhang (Food Bioscience, 2025)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Host preference and mortality caused by the parasitoid Sclerodermus guani on different cerambycid species - Qun Yu; Shuang Li; Yu-Jun Kong; Zuo-Xiang Sun; Dan-Dan Cao; Jian-Rong Wei (BioControl, 2024)

Active tectonic deformation and its seismic–geological significance of boundary faults of the Daxing Uplift and Langgu–Dachang Depression, Beijing Plain, China - Rong-Ying Zheng; Zhong-Yuan Yu; Bai-Xu Chen; Lu-Wei Li; Yi-Cheng Wang (Applied Geophysics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Dual isotope analysis reveals the COVID-19 lockdown impact on nitrate aerosol sources and formation pathways in Shanghai - Rong Wang; Hao Xiao; Yu Xu; Ai-Min Long; Min Zhou; Wen-Kai Guan; Hua-Yun Xiao; Hong-Wei Xiao (Science of The Total Environment, 2024)

Quantitative evaluation of hydrate-based CO2 storage in unsealed marine sediments: Viewpoint from the driving force of hydrate formation and CO2-water contact ability - Hong-Nan Chen; Yi-Fei Sun; Wei-Xin Pang; Ming-Long Wang; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Bo-Jian Cao; Dan Rao; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2024)

Rhodamine and related substances in food: Recent updates on pretreatment and analysis methods - Rong-zhu Du; Yuan Zhang; Yu Bian; Chun-yu Yang; Xue-song Feng; Zhen-wei He (Food Chemistry, 2024)

Fate and drivers of mariculture-derived microplastics from ponds to mangrove forests - Zhen Zhao; Yihua Wei; Yijin Wang; Gen Peng; Eddy Y. Zeng; Kefu Yu; Xiang-Rong Xu; Ruilong Li (Environmental Pollution, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Differential response of soil bacteria and fungi to carbon and respiration components in abandoned grasslands on the Loess Plateau, China - Xingfang Tian; Ying Zhang; Yujie Liang; Rong Fu; Lin Sun; Zhouchang Yu; Jiayi Shi; Ahejiang Sailike; Hongjian Hao; Wei Zhang (Plant and Soil, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

A potential trade-off between reproduction and enhancement of thermotolerance in Liriomyza trifolii populations driven by thermal acclimation - Yu-Cheng Wang; Ya-Wen Chang; Fei Yang; Wei-Rong Gong; Jie Hu; Yu-Zhou Du (Journal of Thermal Biology, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Macroaggregate is crucial in soil carbon and nitrogen accumulation under different vegetation types in the Loess Plateau, China - Hongjian Hao; Yujie Liang; Duo Pian; Ying Zhang; Yaxian Chen; Hongtao Lai; Zhouchang Yu; Ahejiang Sailike; Rong Wang; Ling Cao; Xinhui Han; Wei Zhang (Forest Ecology and Management, 2024)

Simultaneous carbon, nitrogen and phosphorus removal in sequencing batch membrane aerated biofilm reactor with biofilm thickness control via air scouring aided by computational fluid dynamics - Chun-Hai Wei; Xin-Yu Zhai; Yu-Duo Jiang; Hong-Wei Rong; Li-Gong Zhao; Peng Liang; Xia Huang; Huu Hao Ngo (Bioresource Technology, 2024)

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Advances in treatment technologies for silver-containing wastewater - Heng Yu; Hongliang Zhang; Chenyang Zhang; Rong Wang; Siyuan Liu; Ronghao Du; Wei Sun (Chemical Engineering Journal, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

The cytochrome P450 gene CYP4g1 driven by high temperature confers abamectin tolerance on Liriomyza trifolii through promoting cuticular hydrocarbons biosynthesis - Yu-Cheng Wang; Ya-Wen Chang; Hong-Fang Xie; Wei-Rong Gong; Cheng-Dong Wu; Yu-Zhou Du (Pesticide Biochemistry and Physiology, 2024)

Bibliometric study of the application of the chicken embryo chorioallantoic membrane model in cancer research: the top 100 most cited articles - Chang Song; Dan-Dan Xiong; Rong-Quan He; Xiang-Zhi Yong; Zhi-Guang Huang; Yi-Wu Dang; Gang Chen; Yu-Yan Pang; Chun-Yan Zhao; Ning Qu; Dan-Ming Wei (Journal of Comparative Pathology, 2024)

Organic substitution regime with optimized irrigation improves potato water and nitrogen use efficiency by regulating soil chemical properties rather than microflora structure - Xiya Wang; Binggeng Yang; Lingling Jiang; Shicheng Zhao; Mengjiao Liu; Xinpeng Xu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Field Crops Research, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Marine anticancer drugs in modulating miRNAs and antioxidant signaling - Ya-Ting Chuang; Ching-Yu Yen; Jen-Yang Tang; Kuo-Chuan Wu; Fang-Rong Chang; Yi-Hong Tsai; Tsu-Ming Chien; Hsueh-Wei Chang (Chemico-Biological Interactions, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Enhanced anaerobic digestion performance and sludge filterability by membrane microaeration for anaerobic membrane bioreactor application - Chun-Hai Wei; Zheng-Wei Wang; Jian-Hua Dai; Kang Xiao; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Huu Hao Ngo (Bioresource Technology, 2024)

Stochastic community assembly of abundant taxa maintains the relationship of soil biodiversity-multifunctionality under mercury stress - Shuai Du; Xin-Qi Li; Li Bi; Dong Zhu; Hang-Wei Hu; Xiuli Hao; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Soil Ecology Letters, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Early warning of urban heavy metal pollution based on PMF- MeteoInfo model combined with physicochemical properties of dust - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Xinying Zhang; Wei Yu; Rong Yu; Xinyu Liu (Stochastic Environmental Research and Risk Assessment, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Response of soil microbial properties in the life cycle of potatoes to organic substitution regimes in North China - Xiya Wang; Shicheng Zhao; Xinpeng Xu; Mengjiao Liu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Soil and Tillage Research, 2024)

TiO2-x modified Ni/SBA-15 catalysts for dibenzofuran hydrodeoxygenation - Yu-Kun Wang; Hao-Wei Li; Yu-Rong Liu; Zi-Zheng Xie; Zhen-Yi Du; Xing-Bao Wang; Wen-Ying Li (Chemical Engineering Journal, 2024)

Integrated analysis of natural glycans using a versatile pyrazolone-type heterobifunctional tag ANPMP - Yuxia Liu; Tong Yang; Jinqiao Rong; Jinhang Yuan; Lijuan Man; Ming Wei; Jiangbo Fan; Yao Lan; Yinchuan Liu; Guiping Gong; Yu Lu; Xuezheng Song; et al. (Carbohydrate Polymers, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

27-Hydroxycholesterol inhibits trophoblast fusion during placenta development by activating PI3K/AKT/mTOR signaling pathway - Xiaoyan Zhao; Xiaxia Cai; Haiyan Zhu; Qinyu Dang; Qian Yang; Yandi Zhu; Yadi Zhang; Mengling Zhang; Xinyin Jiang; Zhuo Hu; Yuchen Wei; Rong Xiao; et al. (Archives of Toxicology, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

A study of volatiles of young citrus fruits from four areas based on GC–MS and flash GC e-nose combined with multivariate algorithms - Qian Zhang; Rong Xue; Xi Mei; Lianlin Su; Wei Zhang; Yu Li; Jinguo Xu; Jing Mao; Chunqin Mao; Tulin Lu (Food Research International, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Transpiration-mimicking wood-based microfluidic aluminum-air batteries: Green power sources for miniaturized applications - Wei Wang; Liu-Liu Shen; Peiran Wu; Hui Yu; Jiansong Wang; Yipu Xu; Xiangzun Dong; Xuanxuan Cui; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

An airflow-driven system for scalable production of nano-microfiber wrapped triboelectric yarns for wearable applications - Yu Chen; Jie Hua; Yali Ling; Yang Liu; Mingtai Chen; Beomjun Ju; Wei Gao; Amanda Mills; Xiaoming Tao; Rong Yin (Chemical Engineering Journal, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Enhancing simultaneous desulfurization and denitrification efficiency of cement kiln exhaust gas via co-catalytic Fenton oxidation process - Tongsheng Zhang; Hui Peng; Rong Chen; Yiqun Guo; Jiawei Wang; Xinzhi Chen; Jiangxiong Wei; Qijun Yu (Journal of Cleaner Production, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Effects of integrated rice-crayfish farming on soil biodiversity and functions - Jiao Feng; Rong Pan; Hang-Wei Hu; Qiaoyun Huang; Jiaoli Zheng; Wenfeng Tan; Yu-Rong Liu; Manuel Delgado-Baquerizo (Science Bulletin, 2023)

Genome sequence of a Sobemovirus from the feces of Northern Pintail (Anas acuta) - Yu-Rong Wei; Xiao-Yun Mi; Jian-Yong Wu (Virus Genes, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

Bacterial community diversity and underlying assembly patterns along vertical soil profiles in wetland and meadow habitats on the Zoige Plateau, China - Hao-Cai Wang; Jin-Feng Qi; De-Rong Xiao; Yi Wang; Wei-Yu Shi; Hang Wang (Soil Biology and Biochemistry, 2023)

Direct discharge of sewage to natural water through illicitly connected urban stormwater systems: An overlooked source of dissolved organic matter - Ruihua Zhang; Rong Xiao; Feifei Wang; Wenhai Chu; Jinglong Hu; Yu Zhang; Wei Jin; Jan Peter van der Hoek; Zuxin Xu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The acceleration on decolorization of azo dyes by magnetic lignin-based materials via enhancing the extracellular electron transfer - Rong-ping Chen; Xin-yuan Wei; Cheng-hao Gan; Bing-cai Cai; Wen-jie Xu; Shareen Niyazi; Quan Wang; Lei Yu; Hui-hua Min; Qiang Yong (Journal of Environmental Management, 2023)

Mechanical vibration reactor achieves CO2 methanation assisted by ruthenium modified nickel milling balls - Keran Lv; Rui Tu; Lihui Xiao; Wei Wei; Yuchun Xu; Guoqing Ren; Rong Huang; Weiqiao Deng; Tie Yu (Chemical Engineering Journal, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Coupled behaviour and strength prediction of tapered CFDST columns with large hollow ratios for wind turbine towers - Ran Deng; Xu-Hong Zhou; Wei-Dong Ji; Rong-Fu Li; Shuai-Quan Zheng; Yu-Hang Wang (Engineering Structures, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Identification and characterization of goat milk key flavor compounds and their precursors in electron beam irradiation and pasteurization on raw - Chunlu Wen; Ya Chen; Madina; Linlu Zhang; Yue Peng; Bai Rong; Linjie Xi; Shengqi Jiang; Jiangtao Yu; Junqing Bai; Niu Wei; Li Kui; et al. (Innovative Food Science & Emerging Technologies, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

Segmentation of retinal vessels in fundus images based on U-Net with self-calibrated convolutions and spatial attention modules - YiBiao Rong; Yu Xiong; Chong Li; Ying Chen; Peiwei Wei; Chuliang Wei; Zhun Fan (Medical & Biological Engineering & Computing, 2023)

Triterpene constituents from the fruits of Cyclocarya paliurus and their anti-HIV-1 IIIB activity - Wen-Chao Tu; Rong-Hua Luo; En Yuan; Kaunda-Joseph Sakah; Quan-Yu Yang; Wei-Lie Xiao; Yong-Tang Zheng; Mei-Feng Liu (Natural Product Research, 2023)

Effects of scale and contrast of spatial heterogeneity in plant-soil feedbacks on plant growth - Lin Huang; Rong-Yi Chen; Wei Xue; Fei-Hai Yu (Science of The Total Environment, 2023)

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Essential Trace Element Status in Systemic Lupus Erythematosus: a Meta-analysis Based on Case-Control Studies - Hua Wang; Xian-Bao Li; Rong-Gui Huang; Nv-Wei Cao; Hong Wu; Kai-Di Li; Yi-Yu Wang; Bao-Zhu Li (Biological Trace Element Research, 2023)

Intensification of the East Asian winter monsoon resulted in greater preservation of terrestrial organic carbon on the inner shelf of the East China Sea since the last 1400 years - Shuai Liu; Da-Wei Li; Rong Xiang; Meng Yu; Hailong Zhang; Li Li; Meixun Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

Electrophilic components from Xiaoheiyao (rhizomes of Inula nervosa Wall.) alleviate the production of heterocyclic aromatic amines via creatinine inhibition - Xiang-Rong Cheng; Jia-Hui Ma; Issoufou Amadou; Wei Zhao; Yu-Yao Chen; Chen-Xi Zhang; Bin Guan (Food Chemistry, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

The Structure and Function of Glial Networks: Beyond the Neuronal Connections - Hai-Rong Peng; Yu-Kai Zhang; Jia-Wei Zhou (Neuroscience Bulletin, 2023)

Pipeline positioning by the surface-to-borehole electromagnetic induction method in a clayey deposit - Guo-Wei Li; Zhi-Ming Ye; Yang Zhou; Guan-Jun He; Guang-Yu Liu; Xin-Rong He (Applied Geophysics, 2023)

Exosome proteomics study of the effects of traditional cigarettes and electronic cigarettes on human bronchial epithelial cells - Weiling Wang; Rong Zeng; Min Liu; Mulan Chen; Shiqin Wei; Bowen Li; Suhong Yu (Toxicology in Vitro, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Hemin protects UVB-induced skin damage through inhibiting keratinocytes apoptosis and reducing neutrophil infiltration - Fang Bai; Chen Fan; Xi Lin; Hao-Yu Wang; Bing Wu; Chun-Lan Feng; Rong Zhou; Yan-Wei Wu; Wei Tang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Deciphering the electronic-level mechanism of Na+ transport in a graphdiyne desalination membrane with periodic nanopores - Jiongjiong Xu; Kun Meng; Yutao Niu; Changhong Zhang; Kui Xu; Ju Rong; Yan Wei; Xiaohua Yu (Desalination, 2023)

Microwave discharge for rapid introduction of bimetallic-synergistic configuration to conductive catecholate toward long-term supercapacitor - Huiyu Jiang; Jinglin Xian; Rong Hu; Shiyun Mi; Liyun Wei; Guangyu Fang; Zhiao Wu; Siqi Xu; Mingzhao Fan; Kaisi Liu; Huimin Yu; Weilin Xu; et al. (Chemical Engineering Journal, 2023)

The key role of carboxylate ligands in Ru@Ni-MOFs/NF in promoting water dissociation kinetics for effective hydrogen evolution in alkaline media - Cheng-Fei Li; Ting-Yu Shuai; Li-Rong Zheng; Hai-Bo Tang; Jia-Wei Zhao; Gao-Ren Li (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Trophoblast Stem-Cell-Derived Exosomes Alleviate Cardiotoxicity of Doxorubicin via Improving Mfn2-Mediated Mitochondrial Fusion - Junfeng Duan; Xiaoli Liu; Song Shen; Xi Tan; Yi Wang; Lian Wang; Lina Kang; Kun Wang; Zhonghai Wei; Yu Qi; Lei Hu; Biao Xu; et al. (Cardiovascular Toxicology, 2023)
Doxorubicin (Dox) is an anticancer drug widely used in tumor chemotherapy, but it has the side-effect of cardiotoxicity, which is closely related to mitochondrial damage. Mitochondrial dynamics is a quality control mechanism that usually helps to maintain a healthy mitochondrial pool. Trophoblast stem cell-derived exosomes (TSC-Exos) have been shown to protect cardiomyocytes from DOX-induced cardiotoxicity. To explore whether the cardioprotective role is mediated by the regulation of mitochondrial dynamic mechanism, TSC-Exos were isolated from human trophoblast stem cells by ultracentrifugation and characterized by Western blot and transmission electron microscopy. Cellular experiments of H9c2 cardiomyocytes co-cultured with Dox and TSC-Exos were performed in vitro to determine the levels of reactive oxygen species generation and apoptosis level. An animal model of heart failure was established by intraperitoneal injection of Dox in vivo, therapy mice were received additional intracardiac injection of TSC-Exos, then, the cardiac function, cardiomyocyte apoptosis and mitochondrial fragmentation were ameliorated. Histology assays suggest that Dox caused an increased tendency of mitochondrial fission, which was manifested by a decrease in the average size of mitochondria. By receiving TSC-Exos treatment, this effect was eliminated. In summary, these results suggest that TSC-Exos alleviate DOX-induced cardiotoxicity through antiapoptotic effect and improving mitochondrial fusion with an increase in Mfn2 expression. This study is the first to provide a potential new treatment scheme for the treatment of heart failure from the perspective of the relationship between TSC-Exos and mitochondrial dynamics.

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Development of UPLC-MS/MS method for determining hainanmycin in foods of animal origin - Ke-xin Chi; Hang Yu; Ya-hui Guo; Yu-liang Cheng; Yun-fei Xie; Wei-rong Yao (Food Additives & Contaminants: Part A, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Comparative analysis of the structure and function of rhizosphere microbiome of the Chinese medicinal herb Alisma in different regions - Chenbin Wei; Wei Gu; Rong Tian; Fei Xu; Yun Han; Yuanyuan Ji; Tao Li; Yu Zhu; Peilei Lang; Wenqing Wu (Archives of Microbiology, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

How do precipitation events modify the stable isotope ratios in leaf water at Lhasa on the southern Tibetan Plateau? - Yong Wang; Wusheng Yu; Lun Luo; Minghui Li; Xiaoming Liu; Rong Guo; Yaoming Ma; Baiqing Xu; Guangjan Wu; Chengyi Zhao; Zhaowei Jing; Feili Wei; et al. (Isotopes in Environmental and Health Studies, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Isolation of two sesquiterpene glycosides from Sapindus mukorossi Gaertn. with cytotoxic properties and analysis of their mechanism based on network pharmacology - Min-ping Wei; Xiao-wen Zhu; Hang Yu; Yun-fei Xie; Ya-hui Guo; Yu-liang Cheng; He Qian; Wei-rong Yao (Natural Product Research, 2021)

The effectiveness of extended binding affinity of prophage lysin PlyARI against Streptococcus suis infection - Yuyi Xiao; Rong Chen; Min Li; Zitai Qi; Yanfei Yu; Zihao Pan; Huochun Yao; Zhixin Feng; Wei Zhang (Archives of Microbiology, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Neuroprotective Effect of Phthalide Derivative CD21 against Ischemic Brain Injury:Involvement of MSR1 Mediated DAMP peroxiredoxin1 Clearance and TLR4 Signaling Inhibition - Xiao Zou; Xiao-Jia Yang; Yu-Miao Gan; Dong-Ling Liu; Chu Chen; Wei Duan; Jun-Rong Du (Journal of Neuroimmune Pharmacology, 2021)

Mucor rongii sp. nov., a New Cold-Tolerant Species from China - Feirong Bai; Su Yao; Chengshan Cai; Tianci Zhang; Yu Wang; Wei Liu; Baowen Ma; Changyuan Rong; Chi Cheng (Current Microbiology, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Late Cretaceous granitic magmatism and Sn mineralization in the giant Yinyan porphyry tin deposit, South China: constraints from zircon and cassiterite U–Pb and molybdenite Re–Os geochronology - Peng-Cheng Hu; Wei-Guang Zhu; Hong Zhong; Rong-Qing Zhang; Xiao-Yu Zhao; Wei Mao (Mineralium Deposita, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Relationship Between Body Composition and Balance Performance in Older Adults with Hyperkyphosis - Phunsuk Kantha; Shiow-Chwen Tsai; Chien-Wen Hou; Rong-Sen Yang; Pei-Yu Su; Wei-Li Hsu (Journal of Medical and Biological Engineering, 2021)

Infestation and distribution of gamasid mites on Himalayan field rat (Rattus nitidus) in Yunnan Province of Southwest China - Rong Xiang; Xian-Guo Guo; Cheng-Fu Zhao; Rong Fan; Ke-Yu Mao; Zhi-Wei Zhang; Xiao-Bin Huang (Biologia, 2021)

High diversity of planktonic prokaryotes in Arctic Kongsfjorden seawaters in summer 2015 - Yin–Xin Zeng; Wei Luo; Hui–Rong Li; Yong Yu (Polar Biology, 2021)

Heavy metal concentrations and associated health risks in edible tissues of marine nekton from the outer Pearl River Estuary, South China Sea - Chang-Ping Yang; Yan Liu; Bin-Bin Shan; Jing Xu; Wei Yu; Dian-Rong Sun; Zai-Wang Zhang (Environmental Science and Pollution Research, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

Physiological and transcriptional response to heat stress in heat-resistant and heat-sensitive maize (Zea mays L.) inbred lines at seedling stage - De-Chuan Wu; Jia-Fei Zhu; Zhong-Ze Shu; Wei Wang; Cheng Yan; Shan-Bin Xu; De-Xiang Wu; Cheng-Yu Wang; Zhao-rong Dong; Genlou Sun (Protoplasma, 2020)

Ecological analysis of gamasid mites on the body surface of Norway rats (Rattus norvegicus) in Yunnan Province, Southwest China - Zhe Liu; Xian-Guo Guo; Rong Fan; Cheng-Fu Zhao; Ke-Yu Mao; Zhi-Wei Zhang; Yue Zhao (Biologia, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

Sugar transporter genes in grass carp (Ctenopharyngodon idellus): molecular cloning, characterization, and expression in response to different stocking densities - Xiao Liang; Fengying Yan; Yu Gao; Mei Xiong; Haishan Wang; Kommaly Onxayvieng; Rong Tang; Li Li; Xi Zhang; Wei Chi; Marina Piria; Mirna Mrkonjić Fuka; et al. (Fish Physiology and Biochemistry, 2020)

High resolution UPLC-MS/MS method for simultaneous separation and determination of six flavonoids from semen cuscutae extract in rat plasma: application to comparative pharmacokinetic studies in normal and kidney-deficient rats - Wei Zhang; Zhi-Tian Fu; Yao Xie; Zhi-Wen Duan; Yu Wang; Rong-Hua Fan (Natural Product Research, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Triterpene-Enriched Olive Extract as an Immunopotentiator in Black Sea Bream (Acanthopagrus schlegelii) - Jiahuan Rong; Yu Han; Shanjie Zha; Yu Tang; Wei Shi; Xiaofan Guan; Xueying Du; Maolong He; Guangxu Liu (Journal of Ocean University of China, 2020)

Novel dammarane-type saponins from Gynostemma pentaphyllum and their neuroprotective effect - Shao-Fang Xing; Man Lin; Yu-Rong Wang; Tuo Chang; Wei-Ye Cui; Xiang-Lan Piao (Natural Product Research, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Toxicity and metabolism of 3-bromopyruvate in Caenorhabditis elegans - Qiao-ling Gu; Yan Zhang; Xi-mei Fu; Zhao-lian Lu; Yao Yu; Gen Chen; Rong Ma; Wei Kou; Yong-mei Lan (Journal of Zhejiang University-SCIENCE B, 2020)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

Synergistic effects of stromal cell-derived factor-1α and bone morphogenetic protein-2 treatment on odontogenic differentiation of human stem cells from apical papilla cultured in the VitroGel 3D system - Min Xiao; Jun Qiu; Rong Kuang; Beidi Zhang; Wei Wang; Qing Yu (Cell and Tissue Research, 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

The relationship between surface spectral albedo and soil moisture in an arid Gobi area - Zhenchao Li; Jiaxi Yang; Xiaoqing Gao; Ye Yu; Zhiyuan Zheng; Rong Liu; Chao Wang; Xuhong Hou; Zhigang Wei (Theoretical and Applied Climatology, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Diversity of herbaceous plants and bacterial communities regulates soil resistome across forest biomes - Hang‐Wei Hu; Jun‐Tao Wang; Brajesh K. Singh; Yu‐Rong Liu; Yong‐Liang Chen; Yu‐Jing Zhang; Ji‐Zheng He (Environmental Microbiology, 2018)
Summary Antibiotic resistance is ancient and prevalent in natural ecosystems and evolved long before the utilization of synthetic antibiotics started, but factors influencing the large‐scale distribution patterns of natural antibiotic resistance genes (ARGs) remain largely unknown. Here, a large‐scale investigation over 4000 km was performed to profile soil ARGs, plant communities and bacterial communities from 300 quadrats across five forest biomes with minimal human impact. We detected diverse and abundant ARGs in forests, including over 160 genes conferring resistance to eight major categories of antibiotics. The diversity of ARGs was strongly and positively correlated with the diversity of bacteria, herbaceous plants and mobile genetic elements (MGEs). The ARG composition was strongly correlated with the taxonomic structure of bacteria and herbs. Consistent with this strong correlation, structural equation modelling demonstrated that the positive effects of bacterial and herb communities on ARG patterns were maintained even when simultaneously accounting for multiple drivers (climate, spatial predictors and edaphic factors). These findings suggest a paradigm that the interactions between aboveground and belowground communities shape the large‐scale distribution of soil resistomes, providing new knowledge for tackling the emerging environmental antibiotic resistance.

Enriched Expression of Neutral Sphingomyelinase 2 in the Striatum is Essential for Regulation of Lipid Raft Content and Motor Coordination - Laura Hui-Ru Tan; Angela Jin-Rong Tan; Yu-Ying Ng; John Jia-En Chua; Wee-Siong Chew; Sneha Muralidharan; Federico Torta; Bamaprasad Dutta; Siu Kwan Sze; Deron R. Herr; Wei-Yi Ong (Molecular Neurobiology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Functional Investigation of a GRIN2A Variant Associated with Rolandic Epilepsy - Xing-Xing Xu; Xiao-Rong Liu; Cui-Ying Fan; Jin-Xing Lai; Yi-Wu Shi; Wei Yang; Tao Su; Jun-Yu Xu; Jian-Hong Luo; Wei-Ping Liao (Neuroscience Bulletin, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Possible Effects of Electric Fields on a Pair of Spherical Cells - Yu Zheng; Jing Xue; Yang Gao; Lei Dong; Jun-rong Dou; Wei Ma (The Journal of Membrane Biology, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Copper-modified palygorskite is effective in preventing and treating diarrhea caused by Salmonella typhimurium - Da-wei Yao; Ze-zhong Yu; Na Li; Yu-nong Hou; Jia-rong Xu; De-ji Yang (Journal of Zhejiang University-SCIENCE B, 2017)

Bispectral index-guided sedation in transfemoral transcatheter aortic valve implantation: a retrospective control study - Wei He; Rong-rong Huang; Qing-yu Shi; Xian-bao Liu; Jian-an Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

Strawberry MOTHER OF FT AND TFL1 regulates seed germination and post-germination growth through integrating GA and ABA signaling in Arabidopsis - Yang Hu; Yu-Rong Gao; Wei Wei; Kai Zhang; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The meso-mechanism study of gypsum rock weakening in brine solutions - Wei Dong Yu; Wei Guo Liang; Yan Rong Li; Yan Mei Yu (Bulletin of Engineering Geology and the Environment, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Psychrobacter fjordensis sp. nov., a psychrotolerant bacterium isolated from an Arctic fjord in Svalbard - Yin-Xin Zeng; Yong Yu; Hui-Rong Li; Wei Luo (Antonie van Leeuwenhoek, 2015)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Immune protective effect of human alpha-1-antitrypsin gene during β cell transplantation in diabetic mice - Lu Yang; Yu-Ting Liao; Xiao-Fei Yang; Li-Wei Reng; Hui Qi; Fu-Rong Li (Immunologic Research, 2015)

Bacterial composition and spatiotemporal variation in sediments of Jiaozhou Bay, China - Xin Liu; Hang-Wei Hu; Yu-Rong Liu; Ke-Qing Xiao; Fan-Sheng Cheng; Ji Li; Tian Xiao (Journal of Soils and Sediments, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Reference gene selection for real-time RT-PCR normalization in rice field eel (Monopterus albus) during gonad development - Qing Hu; Wei Guo; Yu Gao; Rong Tang; Dapeng Li (Fish Physiology and Biochemistry, 2014)

Fasudil Hydrochloride Protects Neurons in Rat Hippocampal CA1 Region through Inhibiting GluR6–MLK3–JNKs Signal Pathway - Xiu-E Wei; Feng-Yu Zhang; Kai Wang; Qing-Xiu Zhang; Liang-Qun Rong (Cell Biochemistry and Biophysics, 2014)

The Accumulation of Glycine Betaine Is Dependent on Choline Monooxygenase (OsCMO), Not on Phosphoethanolamine N-Methyltransferase (OsPEAMT1), in Rice (Oryza sativa L. ssp. japonica) - Jinde Yu; Yuxiang Li; Wei Tang; Jia Liu; Bao-Rong Lu; Yongsheng Liu (Plant Molecular Biology Reporter, 2014)

Differential expression patterns and a novel interaction factor of Damaged DNA Binding Protein 1A (DDB1A) and DDB1B in Arabidopsis thaliana - Pei Hou; Peng-fei Ren; De-er Zeng; Gui-rong Yu; Wei Tang; Xu Zheng; Jian-ping Yang; Yongsheng Liu (Journal of Plant Biology, 2014)

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

Auditory sexual difference in the large odorous frog Odorrana graminea - Wei-Rong Liu; Jun-Xian Shen; Yu-Jiao Zhang; Zhi-Min Xu; Zhi Qi; Mao-Qiang Xue (Journal of Comparative Physiology A, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Beta Amyloid Peptide (25-35) Leading to Inflammation Through Toll-Like Receptors and the Anti-inflammatory Effect of Genistein in BV-2 Cells - Huan-Ling Yu; Xiao-Ying Li; Xin Zhou; Lin-Hong Yuan; Wei-Wei Ma; Yuan-Di Xi; Xia Zhao; Jian Wu; Rong Xiao (Journal of Molecular Neuroscience, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

A functional polymorphism, rs28493229, in ITPKC and risk of Kawasaki disease: an integrated meta-analysis - Jiao Lou; Sanqing Xu; Li Zou; Rong Zhong; Ti Zhang; Yu Sun; Xuzai Lu; Li Liu; Chuanqi Li; Li Wang; Guanglian Xiong; Wei Wang; et al. (Molecular Biology Reports, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Magma mingling and chemical diffusion in the Taojiang granitoids in the Hunan Province, China: evidences from petrography, geochronology and geochemistry - Kai-Xing Wang; Pei-Rong Chen; Wei-Feng Chen; Hong-Fei Ling; Kui-Dong Zhao; Zhi-Qiang Yu (Mineralogy and Petrology, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Synthesis and anticonvulsant activity of 8-alkoxy-5,6-dihydro-4H-benzo[f][1,2,4]triazolo[4,3-a]azepine derivatives - Wen-Bin Zhang; Rong-Bi Han; Wei Zhang; Ri-Shan Jiang; Feng-Yu Piao (Medicinal Chemistry Research, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Molecular detection of Torque teno mini virus (TTMV) in China - Caixia Zhu; Rong A; Congli Yuan; Ying Yu; Li Cui; S. D. Tang; Zhiwei Liu; Wei Zhao; Xiuguo Hua (Virus Genes, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Decreased expression of Beclin-1 and LC3 in human lung cancer - Zi-Feng Jiang; Li-Jie Shao; Wei-Min Wang; Xue-Bo Yan; Rong-Yu Liu (Molecular Biology Reports, 2012)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Benefits of a symbiotic association with endophytic fungi are subject to water and nutrient availability in Achnatherum sibiricum - An Zhi Ren; Xia Li; Rong Han; Li Jia Yin; Mao Ying Wei; Yu Bao Gao (Plant and Soil, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Promoter Analysis of Mouse Scn3a Gene and Regulation of the Promoter Activity by GC Box and CpG Methylation - Guang-Fei Deng; Jia-Ming Qin; Xun-Sha Sun; Zu-Ying Kuang; Tao Su; Qi-Hua Zhao; Yi-Wu Shi; Xiao-Rong Liu; Mei-Juan Yu; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Journal of Molecular Neuroscience, 2011)

Validation and dissection of quantitative trait loci for leaf traits in interval RM4923-RM402 on the short arm of rice chromosome 6 - BO SHEN; WEI-DONG YU; JING-HONG DU; YE-YANG FAN; JI-RONG WU; JIE-YUN ZHUANG (Journal of Genetics, 2011)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Comparison of DNA extraction methods for the PCR-single-strand-conformation polymorphism analysis of kefir - Shu-Jun Chen; Qing Wang; Jian-Rong Han; Yu Wang; Zhi-Wei Li (World Journal of Microbiology and Biotechnology, 2011)

Methotrexate ameliorates pristane-induced arthritis by decreasing IFN-γ and IL-17A expressions - Wei-kun Hou; Lie-su Meng; Fang Zheng; Yu-rong Wen; Wen-hua Zhu; Cong-shan Jiang; Xiao-jing He; Yan Zhou; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2011)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Research of the ATPase’s rotation catalysis stochastic transition dynamics - Yan Zheng; Ming-Jian Yang; Wei-Xia Wu; Kun Yu; Ying-Rong Han; Yong Zhan; Yan-Bin Huang (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Human signal peptide had advantage over mouse in secretory expression - Xue-wu Xu; Shu-jun Pei; Xue-rong Miao; Wei-feng Yu (Histochemistry and Cell Biology, 2009)

Direct visualization of bacterial infection process in nematode hosts by an improved immunocytochemical method - Bao-Yu Tian; Chong-Rong Ke; Wei Huang; Ke-Qin Zhang; Jian-Zhong Huang (World Journal of Microbiology and Biotechnology, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Depressive-like behavior in mice recently recovered from motor disorders after 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Sha Ma; Wei Zhou; Zheng Wei; Yu-Xiang Zheng; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2008)

A preliminary study on the teratogenesis of dexamethasone and the preventive effect of vitamin B12 on murine embryonic palatal shelf fusion in vitro - Sheng-jun Lu; Wei He; Bing Shi; Tian Meng; Xiao-yu Li; Yu-rong Liu (Journal of Zhejiang University-SCIENCE B, 2008)

Evaluation of FORS-D Analysis: A Comparison with the Statistically Significant Stem-loop Potential - Chi-Yu Zhang; Ji-Fu Wei; Jian-Sheng Wu; Wen-Rong Xu; Xiao Sun; Shao-Heng He (Biochemical Genetics, 2008)

Activation of Helicobacter pylori inorganic pyrophosphatase and the importance of Cys16 in thermostability, enzyme activation and quaternary structure - Mon-Juan Lee; Haimei Huang; Wei Lin; Ray-Rong Yang; Chien-Liang Liu; Chung-Yu Huang (Archives of Microbiology, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Berbamine induces apoptosis in human hepatoma cell line SMMC7721 by loss in mitochondrial transmembrane potential and caspase activation - Guan-yu Wang; Jia-wei Zhang; Qing-hua Lü; Rong-zhen Xu; Qing-hua Dong (Journal of Zhejiang University-SCIENCE B, 2007)

Ile118Val genetic polymorphism of CYP3A4 and its effects on lipid-lowering efficacy of simvastatin in Chinese hyperlipidemic patients - An Wang; Bang-Ning Yu; Chen-Hui Luo; Zhi-Rong Tan; Gan Zhou; Lian-Sheng Wang; Wei Zhang; Zhi Li; Jie Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2005)

Pharmacodynamics and Toxicodynamics of Drug Action: Signaling in Cell Survival and Cell Death - Ah-Ng Tony Kong; Sandhya Mandlekar; Rong Yu; Wei Lei; Adedigbo Fasanmande (Pharmaceutical Research, 1999)

Activation of Signal Transduction Kinases by Tamoxifen - Jauh-Lin Duh; Rong Yu; Jie-Jun Jiao; George A. Matwyshyn; Wei Li; Tse-Hua Tan; A.-N. Tony Kong (Pharmaceutical Research, 1997)